Journal PERAN PAJAK RESTORAN DAN PAJAK HOTEL TERHADAP SUMBER PENDAPATAN ASLI DAERAH KOTA BOGOR TAHUN 2017 – 2021 - zai, grace (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to clarify the role of restaurant and hotel taxes from 2017 to 2021. The type of research data that the researcher uses is a quantitative descriptive approach and uses secondary data, the data collected is in the form of a realization report in the city of Bogor from 2017 to 2021 to see the contribution of each variable. The analytical calculation method of this study uses multiple linear analysis and data processing is carried out using SPSS version 26. In analyzing research data, the classical assumption test is used, the partial test (T test), the simultaneous test (F test), and the results of the coefficient of determination test ( R²). This study shows the results where the restaurant tax value is partially 0.956 and the hotel tax is 0.915, meaning that it will have a significant positive effect on the city of Bogor. from 2017 to 2021. Meanwhile, the results of the simultaneous test show that the independent variable is not an explanatory factor for the dependent variable at the same time. Therefore, the regional origins income can be supported by other variables such as land tax and building tax, advertisement tax, entertainment tax and so on.